2008
DOI: 10.1002/jbm.a.31788
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicone surface roughness and hydrophobicity on adhesion and colonization of Staphylococcus epidermidis

Abstract: Bacterial adhesion and colonization are complicated processes that depend on many factors, including surface chemistry, hydrophobicity, and surface roughness. The contribution of each of these factors has not been fully elucidated because most previous studies used different polymeric surfaces to achieve differences in properties. The objective of this study was to modify hydrophobicity and roughness on one polymeric surface, eliminating the confounding contribution of surface chemistry. Mechanically assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 41 publications
5
76
0
2
Order By: Relevance
“…4b); therefore, the possible observed trend is only dependent on roughness. This is supported by a previous study reporting a positive correlation of increasing attachment with roughness [63]. Fig.…”
Section: Mechanisms Of Attachmentsupporting
confidence: 89%
“…4b); therefore, the possible observed trend is only dependent on roughness. This is supported by a previous study reporting a positive correlation of increasing attachment with roughness [63]. Fig.…”
Section: Mechanisms Of Attachmentsupporting
confidence: 89%
“…104, 105 Tang et al reported that surface roughness significantly affects the adhesion of S. epidermidis on silicon surfaces only when the root-meansquare roughness was higher than 200 nm. 106 The studies of influence of physical structuring of surface nanofeatures on bacterial adhesion further revealed the role of surface roughness in bacterial adhesion. Whitehead et al 107 measured the bacterial adhesion on Si wafers coated with titanium having featured surface pit sizes of 0.2, 0.5, 1, 2 mm in diameter and different depths, resulting in R a values ranging from 45 to 220 nm.…”
Section: Biomaterials Surface Properties Affect Bacterial Adhesionmentioning
confidence: 99%
“…In vitro Hydrophobic surface resulted in higher attachment of bacterium [108] In vitro Up to 89% reduction in bacterial adhesion on hydrophobic surface [107,109] P Triclosan and bronopol S. aureus In vitro 80% of cells were killed but no effect in terms of colonization [30] Escherichia coli In vitro Triclosan was more effective than bronopol [30] Bronopol, bezalkonium chloride and chlorohexidine S. aureus and E. coli…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%